Pathogenic role of intestinal microflora changes in patients with irritable bowel syndrome and treatment options - Ye. A. Poluektova; S. Yu. Kuchumova; O. S. Shifrin; A. A. Sheptulin; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyse of publications on qualitative and quantitative changes in pattern of intestinal microflora in patients with irritable bowel syndrome (IBS) and options of its treatment by pre-, pro-, and symbiotic drugs.Key points. In the last years more and more data appear on changes in qualitative and quantitative spectrum of intestinal microflora in combination to low degree inflammation of colonic mucosa at IBS that allowed to reconsider standard concepts on pathogenesis of this functional disorder. Agents restoring intestinal microflora balance are effective for symptom relief of this disease.Conclusion. The analysis of the information concerning disorder of qualitative and quantitative structure of intestinal microflora at IBS, mechanisms of action of pre-, pro- and synbiotics, allows to expand essentially treatment options of this disease.